Rhizosphere‐Scale Quantification of Hydraulic and Mechanical Properties of Soil Impacted by Root and Seed Exudates. Issue 1 (15th February 2018) - Naveed, M.; Brown, L.K.; Raffan, A.C.; George, T.S.; Bengough, A.G.; Roose, T.; Sinclair, I.; Koebernick, N.; Cooper, L.; Hallett, P.D.
Abstract : Core Ideas: We hypothesized that plant exudates gel soil particles and on drying enhance water repellency. This has been carried out using rhizosphere‐scale mechanical and hydraulic measurements. Plant exudates enhanced soil hardness and modulus of elasticity as chia seed > maize root > barley root. Plant exudates caused measureable decreases in soil wetting rates through water repellency. Using rhizosphere‐scale physical measurements, we tested the hypothesis that plant exudates gel together soil particles and, on drying, enhance soil water repellency. Barley ( Hordeum vulgare L. cv. Optic) and maize ( Zea mays L. cv. Freya) root exudates were compared with chia ( Salvia hispanica L.) seed exudate, a commonly used root exudate analog. Sandy loam and clay loam soils were treated with root exudates at 0.46 and 4.6 mg exudate g −1 dry soil and chia seed exudate at 0.046, 0.46, 0.92, 2.3 and 4.6 mg exudate g −1 dry soil. Soil hardness and modulus of elasticity were measured at −10 kPa matric potential using a 3‐mm‐diameter spherical indenter. The water sorptivity and repellency index of air‐dry soil were measured using a miniaturized infiltrometer device with a 1‐mm tip radius. Soil hardness increased by 28% for barley root exudate, 62% for maize root exudate, and 86% for chia seed exudate at 4.6 mg g −1 concentration in the sandy loam soil. For the clay loam soil, root exudates did not affect soil hardness, whereas chia seed exudate increased soil hardness by 48% at 4.6 mg g −1 concentration. Soil water repellency increased by 48% for chia seed exudate and 23% for maize root exudate but not for barley root exudate at 4.6 mg g −1 concentration in the sandy loam soil. For the clay loam soil, chia seed exudate increased water repellency by 45%, whereas root exudates did not affect water repellency at 4.6 mg g −1 concentration. Water sorptivity and repellency were both correlated with hardness, presumably due to the combined influence of exudates on the hydrological and mechanical properties of the soils.